Soleus Muscle Flap for Coverage of Soft Tissue Defect of Leg - Parajuli, Nirajan Prasad; Khan, Md Irshad; Yadav, Krishna Kant; Sah, Rajeev Kumar (Medical Journal of Eastern Nepal, 2023)
Background: Open tibia fracture with soft tissue loss at the fracture site is and always a challenging problem for orthopedic surgeons to deal with. Soleus flap is an important option for such defects out of many other options.Methods: Retrospective descriptive study in which twenty-one patients with open tibia fracture with soft tissue defect at fracture site requiring flap coverage were included in the study. In all 21 patients, the soleus muscle flap was done.Results: Out of 21 patients, in 16 patients medial hemisoleus flap was done and in five composite soleus muscle flap was done. The average age of the patients was 37.8 years, and the right leg was more involved. In all patients, bone coverage was achieved. Three patients required debridement and mobilization of flap due to infective necrosis at the margin. The mean follow-up was 12 months.Conclusion: Soleus muscle flap is a good and versatile flap for the coverage of soft tissue defects of the leg exposing bone or fracture.